Antioxidant and Cytotoxic Properties of Soft Coral Nepthea sp. - Baru Sadarun; Nur Syifa Rahmatika; Agung Wibawa Mahatva Yodha; Adryan Fristiohady; Andini Sundowo; Syarul Nataqain Baharum; Idin Sahidin (Marine Science Department Diponegoro University, 2022)
Soft coral Nepthea sp. grows in the seas of South-East Sulawesi, Indonesia. However, information on the chemical and pharmaceutical aspects of this genus is still limited. Therefore, this research aims to explore the chemical contents and biological activities of Nepthea sp. The sample was collected from the waters of Saponda Island by SCUBA diving. It was extracted by ethyl acetate and fractionated using vacuum liquid chromatography. The chemical content was analyzed by phytochemical screening, LC-MS/MS analysis, Total Phenolics Content and Total Flavonoids Contents. Antioxidant potency was evaluated by DPPH (2,2-diphenyl-1-picrylhydrazyl) radicals and ABTS (2,2’-azino-bis-3-ethylbenzthiazoline-6-sulphonic acid). Cytotoxicity property was analyzed by MTT (3-(4,5-Dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide) assays. The result showed that the fractionation of Nepthea ethylacetate extracts produced six fractions (A-F). Fractions A and B contain non-polar compounds. Based on LC-MS/MS data, the non-polar compounds in Fraction A and B include achillin, atractylenolide II, buthyl isobuthyl phthalate, rengyolester, 2a-acetoxycostic acid, ocotillol acetate, petasitolone and some unidentified compounds that are C33H58O4, C15H21NO, C21H33NO, and C16H20O4. In general, the antioxidant and cytotoxic properties of all samples are in the weak category, however, when examined for each sample, the antioxidant properties of fraction B is slightly better than fraction A based on the IC50 value of DPPH and ABTS. Cytotoxicity of Fraction A is better than Fraction B against Breast Cancer cell lines MCF-7. The non-polar fraction of Nepthea sp. can be developed as raw material for the discovery of new compounds, antioxidant and anticancer agents, especially breast cancer.